Stress Testing for Assessing the Impact of Market Shocks on Banks' Financial Stability - S. Andrushchenko, Yuliy; N. Salin, Victor; G. Tretyakova, Olga; P. Shpakovskaya, Elena; I. Larionova, Elena; I. Chinaeva, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
Modern processes of integration and globalization not only provide new development and growth prospects but also serve as a transfer mechanism for various shocks that negatively affect the economic development of countries. For instance, one of the recent shocks was associated with a sharp drop in oil prices at the end of 2014. These changes affected the financial stability of the banking sector that is generally responsible for the functioning of the entire economy.